Исследование фотоэлектрических характеристик микрофототерминала - Karimov, A. V.; Yodgorova, D. M.; Buzrukov, U. M.; Mirdjalilova, M. A.; Boltaeva, Sh. Sh. (PE "Politekhperiodika", Book and Journal Publishers, 2006)
The results of a study of the photoelectric characteristics of a microphoto terminal consisting of a photodiode–diode structure with oppositely connected photo- and dark diodes are presented. It is shown that in the photogalvanic mode its parameters undergo insignificant changes, while in the photoreceptive mode it exhibits high photosensitivity. The proposed design of the elements is of interest for switching several photoelectric structures with minimal losses.